Analyzing Employee Retention in Growing Indonesian MSMEs: Factors such as Compensation, Career Opportunities, and Leadership Styles - Umpusinga, Hasrun Afandi; Utami, Eva Yuniarti; Widiawati, Wilda; Hafidurrahman, Moh (International Journal of Business, Law, and Education, 2024)
This study looks into the intricate connections between leadership style, pay, career possibilities, employee performance, staff retention, and the productivity of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia. The study employed a quantitative research methodology using Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis to gather and examine data from 487 employees of MSMEs in Indonesia. Significant conclusions emerged from the data, including the following: high employee performance positively impacts employee retention and MSME performance, structured career opportunities enhance employee outcomes, remuneration impacts both employee performance and retention, and employee retention impacts MSME performance. These results highlight HRM strategies' role in motivating workers' productivity and retention, boosting MSMEs' overall success in the Indonesian market.